Artistic and Intellectual Practices in Contemporary China
XI, 317 p. 6 illus., 2 illus. in color.
Keywords: The edited book elevates a chorus of voices from domestic and international intellectuals, artists, curators, and historians in a dialogue that reframes Chinese art from 1949 to the present. Part I offers critical academic complications of the story of Chinese art from the 1950s to the present as one singularly defined and stifled by political revolution. It traces important continuities and early examples of contemporary art practice to the Party’s birth and consolidation of power from the 1920s onwards. It relates the formation of contemporary art to the historical course of intellectual practice in China from 1949. Part II proposes China as an “issue” requiring historical interrogation rather than an inviolable entity. It questions the efficacy of “Asia” as a term, presents case studies of independent publishers that challenged tightly crafted historical narratives, and wraps up with incisive reflections on the challenges confronting creatives and historians in China today. With chapters ranging from peer-reviewed scholarship to cuttingly humorous personal anecdotes, its contributing authors give rare, first-hand accounts of navigating pertinent historical and current situations, including censorship, China’s il/liberalism, and COVID-19. This book offers readers an ear to heretofore closed-door conversations in leading modern and contemporary art spaces. Carol Yinghua LU was born in 1977 in Chaozhou, Guangdong. LU is an art historian and a curator. She received her Phd degree in art history from the University of Melbourne in 2020. She is the director of Beijing Inside-Out Art Museum.